Lithium‐Ion Batteries: Discovery of an Unexpected Metal Dissolution of Thin‐Coated Cathode Particles and Its Theoretical Explanation (Adv. Theory Simul. 5/2020). Issue 5 (7th May 2020) - He, Yufang; Pham, Hiep; Gao, Yan; Patel, Rajankumar L.; Sarkar, Susmita; Liang, Xinhua; Park, Jonghyun
Abstract : It is believed that a thin coating layer deposited via atomic‐layer deposition onto lithium‐ion battery active material particles can prevent the metal dissolution degradation. However, in article number 2000002, Jonghyun Park and co‐workers observe that while an Al2 O3 coating can prevent dissolution a CeO2 coating intensifies it. They employ first‐principles calculations by calculating the manganese vacancy formation energy, crystal orbital overlap population (COOP) analysis, Mn–O bond length, and projected density of state (PDOS) analysis.